ANALISIS PENGETAHUAN TENTANG KOMPETENSI KEPRIBADIAN GURU PAUD DI KECAMATAN LIMA PULUH KOTA PEKANBARU - Ariyani, Desi; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the knowledge of personal competence early childhood teachers in the district Fifty Pekanbaru. The population and the sample in this study were all early childhood teachers who trained S1 counted 70 people. The data collection techniques were used to test. Data analysis techniques in this study with a percentage formula. The survey knowledge of personal competency early childhood teachers in the district Fifty Pekanbaru overall indicator score obtained in 1481 with a rate of 91.95% in the very good category. Although the positions of each indicator, the indicator acts as per the norm, religious, legal, social and national culture of Indonesia achieved a rate of 93.21% in the very good category, presenting the indicators yourself as a person who is honest , noble, and an example for early childhood and community-acquired percentage of 93.42% in the very good category, the indicators present itself as a stable, stable, mature, wise, prudent and beribawa achieved a rate of 92.57% in the very good category, showing work ethic, high responsibility, self-confidence, and are proud to be a teacher obtained a percentage of 90.57% in the very good category, enforcing the code of ethics of teachers achieved a rate of 90% in the very good category.Keywords: Knowledge, Competence Personality